P‐32: Novel Gate Driving Circuit Integrated within Active Area Based on Amorphous Oxide TFT. Issue 1 (25th September 2020) - Wang, MingXin; Zhou, Liufei; Wang, Zhijun; Xu, Shangjun; Shu, Yang; Wang, Huaipei; Yuan, Ling; Bian, Cunjian; Fei, Mi
Abstract : In this paper, we present a novel display panel framework and gate driving circuit which located within active area. The uniformity of gate driving circuit which evenly distributed in the whole pixel area is guaranteed by the adoption of BCE amorphous oxide TFT.